The Effectiveness of the Financial Accounting System in Assessing Regional Economic Health - Nurnaningsih, Rita (PT. Anagata Sembagi Education, 2025)
This study aims to examine the effectiveness of regional financial accounting systems in assessing and supporting the economic health of local governments. Using a quantitative approach with survey data collected from selected regional finance departments, the research investigates the relationship between accounting system effectiveness and key fiscal indicators, including local revenue performance, expenditure efficiency, and fiscal dependency. The findings reveal that regions with well-functioning, integrated accounting systems tend to demonstrate stronger fiscal performance and better financial planning. Additionally, the study highlights the strategic role of accounting information in supporting evidence-based policymaking and improving transparency and accountability. However, disparities in implementation, especially between urban and rural regions, remain a significant challenge due to gaps in technology infrastructure and human resources. The study concludes by emphasizing the need for institutional reform, leadership engagement, and capacity building to enhance the overall utility of financial accounting systems as a tool for sustainable regional development.